Pengaruh Pendekatan Realistic Mathematics Education dengan Konteks Budaya Melayu Kepulauan Riau Terhadap Hasil Belajar Siswa - Melisawati, Melisawati; Izzati, Nur; Rahmatina, Desi (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
The aim of this research is to analyze the influence of the Realistic Mathematic Education approach in the context of Malay culture in the Riau Islands on the learning outcomes of class VIII SMP students on flat-sided geometric building material. Quasy experiment with non-equivalent control group design was applied in this research. The research sample, namely classes VIIIA and VIIIB, was selected from all class VIII students at SMP Negeri 4 Bintan with a total of 99 students using a cluster sampling technique. The test instrument used is essay questions to measure student learning outcomes. Data was collected using a test technique, namely pretest-posttest and analyzed using an independent sample t-test with a significance level of 5%. Through the research results, a sig value was obtained. equal to 0.0125 and it is known that 0.0125 < 0.05 ( ). So it is found that the sig value. < 0.05 then H0 is rejected, meaning that the average difference in students' final learning outcomes has a significant difference. It can be concluded that there is an influence of the Realistic Mathematic Education learning approach in the Malay cultural context of the Riau Islands on student learning outcomes.